Tinjauan Yuridis Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 dalam Hal Perubahan Ketentuan Pasal 2 dan 3 Undang-Undang Nomor 20 Tahun 2001 tentang Tindak Pidana Korupsi - Angga Alfiyan (Law Faculty of Universitas Bandar Lampung, 2018)
Implementation of the Constitutional Court Decision Number 25 / PUU-XIV / 2016 In the matter of Amendments to the Provisions of Article 2 and 3 of Law Number 20 of 2001 concerning Corruption Crimes and Legal Effects Arising from the Decision of the Constitutional Court Decision Number 25 / PUU-XIV / 2016 in The Amendment to the Provisions of Article 2 and 3 of Law Number 20 of 2001 concerning Corruption. The results of this study are, Opinion of the word